Urea and Fermentrol® additives for forage sorghum silage - Janicki, B.; Bolsen, K.; Hinds, M.; Ilg, H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Adding urea to forage sorghum greatly increased the ensiling temperature, produced a more rapid and extensive fermentation, and resulted in more shrink loss in the silo. Fermentrol®, an enzyme-inoculant additive, had very little affect on the silage temperature or chemical composition, but it did reduce the shrink loss. Calves red urea-treated silage had the poorest performance. Control and Fermentrol® silages each produced about 90 lb of calf gain per ton of crop ensiled, however urea silage produced only 60 lb. All three silages had short bunk lives throughout the trial.
Keywords: Beef; Urea; Additives; Sorghum silage